2019
DOI: 10.1177/0891241619854123
|View full text |Cite
|
Sign up to set email alerts
|

Digital Ethnography in an Age of Information Warfare: Notes from the Field

Abstract: In this article we engage the nature and role of the Internet in ethnographic research and reflect on how ethnographic methodologies may be adapted when researching digital forms of communication. We further consider how recent shifts in both the production and dissemination of textual discourse in networked media environments complicates conventional approaches to digital ethnography. Drawing on examples from our field research, our principal objective is to apply a Foucauldian structural perspective to David… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…From methodological perspectives, we examined the existing digital discourses that are created or shared by the migrant workers themselves (i.e., we did not provide any prompt for discussion or participation to the workers). Scholars noted that a “democratized” access to digital spaces often aids cocultural populations to enunciate counterhegemonic discourses, which, in turn, potentially yield a candid and thick data as well as enrich the overall research processes ( Kavanaugh & Maratea, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From methodological perspectives, we examined the existing digital discourses that are created or shared by the migrant workers themselves (i.e., we did not provide any prompt for discussion or participation to the workers). Scholars noted that a “democratized” access to digital spaces often aids cocultural populations to enunciate counterhegemonic discourses, which, in turn, potentially yield a candid and thick data as well as enrich the overall research processes ( Kavanaugh & Maratea, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…
Context refers to the social situations surrounding the document in question, independently of the content of the document itself … Process refers to the exercise of document creation from its initial production to its internal organization … Emergence refers to the gradual shaping of meaning through understanding and interpretation. (Kavanaugh and Maratea 2019:7, emphasis in original; see also Altheide and Schneider 2013:13–16)
While a focus on the collection and evaluation of narrative data is similar to more conventional forms of content analysis, ethnographic content analysis attempts to identify the communication of meaning as reflected in the “frequency of occurrence of certain symbols into summary judgments and comparisons of the content of discourse” (Starosta 1984:185), in hopes of identifying “underlying meanings, patterns, and processes” contained in the texts being examined (Altheide 2000:290). Emphasis is on analyzing documents inductively without predetermined constraints, “to be systematic and analytic, but not rigid,” and to facilitate “ constant discovery and constant comparison of relevant situations, settings, styles, images, meanings, and nuances” (Altheide 1987:68; emphasis in original).…”
Section: Methodsmentioning
confidence: 99%
“…Context refers to the social situations surrounding the document in question, independently of the content of the document itself … Process refers to the exercise of document creation from its initial production to its internal organization … Emergence refers to the gradual shaping of meaning through understanding and interpretation. (Kavanaugh and Maratea 2019:7, emphasis in original; see also Altheide and Schneider 2013:13–16)…”
Section: Methodsmentioning
confidence: 99%
“…Digital ethnographers highlighted three characteristics of online interactions on social media platforms, which in turn shape how people discuss and make sense of degrees. Kavanaugh and Maratea (2020) found that online users gather simultaneously in specific sites, form online crowds, and reply to one another in particular threads or topics. For example, people tweet their opinions and create hashtags on Twitter to express their political views.…”
Section: Digital Ethnography: Self-representation Censorship and Ways Of Talking Onlinementioning
confidence: 99%